“PHE in Action”: Development and Modeling of an Intervention to Improve Patient Engagement among Older Adults - Menichetti, Julia; Graffigna, Guendalina (Frontiers in Psychology, 2016)
The increasing prevalence of chronic conditions among older adults constitutes a major public health problem. Thus, changes in lifestyles are required to prevent secondary conditions and sustain good care practices. While patient engagement received great attention in the last years as key strategy to solve this issue, to date no interventions exist to sustain the engagement of older chronic patients towards their health management. This study describes the design, development, and optimization of PHEinAction, a theoretically-driven intervention program to increase patient engagement in older chronic populations, and, consequently, to foster healthy changes that can help reduce risks of health problems. The development process followed the UK Medical Research Council’s (MRC) guidelines and involved selecting the theoretical base for the intervention, identifying the relevant evidence-based literature, and conducting exploratory research to qualitatively evaluate program’s feasibility, acceptability and comprehension. The result was a user-endorsed intervention designed to improve older patients’ engagement in health management based on the theoretical framework of the Patient Health Engagement (PHE) model. The intervention program, which emerged from this process, consisted of two monthly face-to-face 1-hour sessions delivered by a trained facilitator and one brief telephonic consultation, and aimed to facilitate a range of changes for patient engagement (e.g., motivation to change, health information seeking and use, emotional adjustment, health behaviors planning). PHEinAction is the first example of a theoretically-based patient engagement intervention designed for older chronic targets. The intervention program is based on psychological theory and evidence; it facilitates emotional, psychological, and behavioral processes to support patient engagement and lifestyle change and maintenance. It provides estimates of the extent to which it could help high-risk groups engage in effective health management and informs future trials.